2023
DOI: 10.1002/pssr.202200496
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Modeling of Charge‐Trapping Defects in Amorphous Ge‐Sb‐Te Phase‐Change Memory Materials

Abstract: Phase-change memory materials based on Ge-Sb-Te alloys encode stored digital binary data as metastable structural states of the chalcogenide material with contrast in optoelectronic properties, and they correspond to a contender for next-generation, nonvolatile electronic-memory technology. [1] Moreover, they are also promising candidates for neuromorphic and in-memory computing applications, as well as for new storage-class memory devices. [2] The function of phase-change random-access electronic-(optical-)me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Melting kinetics studies have revealed a melting process for the T material state, wherein a crystallized cluster splits into different structural entities with a medium-range order, i.e., cubes and planes of atoms, which then divide into separate four-fold rings that finally disintegrate as the PCM layer melts. [61][62][63] This mechanism can be expanded to the continuous melting induced in a sequence of targeted-amplitude partial-reset pulses. At the glass-crystal interface, heating the PCM layer beyond the melting point results in a substantial population of structural defects, e.g., dangling bonds, a "thermal shock" in the crystallized PCM layer and bond breaking.…”
Section: Resultsmentioning
confidence: 99%
“…Melting kinetics studies have revealed a melting process for the T material state, wherein a crystallized cluster splits into different structural entities with a medium-range order, i.e., cubes and planes of atoms, which then divide into separate four-fold rings that finally disintegrate as the PCM layer melts. [61][62][63] This mechanism can be expanded to the continuous melting induced in a sequence of targeted-amplitude partial-reset pulses. At the glass-crystal interface, heating the PCM layer beyond the melting point results in a substantial population of structural defects, e.g., dangling bonds, a "thermal shock" in the crystallized PCM layer and bond breaking.…”
Section: Resultsmentioning
confidence: 99%